2015
DOI: 10.1007/s10995-015-1764-4
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Pre-pregnancy BMI, and Gestational Weight Gain in Puerto Rican Women

Abstract: Objectives To describe the dietary patterns in pregnant woman and determine the association between diet factors, pre-pregnancy Body Mass Index (BMI) and socio-demographic characteristics with gestational weight gain (GWG). Methods This is a secondary analysis of a longitudinal cohort study of pregnant women exploring the risk factors for preterm birth, the Puerto Rico Testsite for Exploring Contamination Threats program. Recruitment was conducted during 2011–2014. Data was collected from multiple sources. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…Although our Mixed diet pattern was heterogeneous in nature, the high added sugar content may be driving this association and potentially negate some of the benefits of the “healthier” items such as whole grains and nuts. This is supported by previous studies in which higher intakes of a Margarine, Sugar and Snacks diet pattern and more frequent consumption of high-sugar fruit drinks have been positively associated with excessive GWG [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although our Mixed diet pattern was heterogeneous in nature, the high added sugar content may be driving this association and potentially negate some of the benefits of the “healthier” items such as whole grains and nuts. This is supported by previous studies in which higher intakes of a Margarine, Sugar and Snacks diet pattern and more frequent consumption of high-sugar fruit drinks have been positively associated with excessive GWG [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 81%
“…In high-income countries (HICs) some studies have shown that a high protein: carbohydrate ratio, partly driven by a reduced added-sugar intake, is associated with lower GWG and that high adherence to a margarine, sugar and snacks dietary pattern is associated with excessive GWG when compared to low adherence to this pattern [ 23 , 24 ]. Additionally, in Puerto Rican women, frequent consumption of high-sugar fruit drinks was associated with excessive GWG [ 25 ]. To our knowledge, however, dietary patterns and their relationships with maternal nutritional status prior to and during pregnancy are yet to be explored in urban African populations where the associations may be further complicated by existing co-morbidities, such as the high burden of HIV, which may independently predict low pre-pregnancy BMI, poor GWG and micronutrient deficiencies [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further to the data from our setting, dietary patterns high in processed foods and/or sugar have been associated with maternal adiposity, GDM risk, and birth size in high‐income and low‐ and middle‐income countries (LMICs; Coelho et al, ; Englund‐Ögge et al, ; Guilloty et al, ; Sedaghat et al, ; Tielemans et al, ). It has also been suggested that the influence of maternal dietary practices on infant adiposity may persist into childhood.…”
Section: Discussionmentioning
confidence: 69%
“…Studies of the developmental origins of health and disease have shown that the nutritional environment that mothers provide during pregnancy is important for the optimal health, development, and long term chronic disease risk of the baby [ 1 , 2 ]. In women, data from prospective cohort studies has indicated that during pregnancy, consuming a diet rich in fruits, vegetables, lean meat/fish, and wholegrains while being low in energy dense–nutritionally poor food is associated with a lower risk of exceeding the Institute of Medicine (IOM) gestational weight gain (GWG) guidelines [ 3 ], and lower risk of developing complications such as gestational hypertension [ 4 ] or gestational diabetes [ 5 , 6 , 7 ]. In 2016, the Society for Obstetricians and Gynaecology Canada released a report on the consensus on female nutrition across the life-course in order to achieve optimal health for both women and their offspring [ 8 ].…”
Section: Introductionmentioning
confidence: 99%